2010
DOI: 10.1111/j.1582-4934.2009.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fatty acid biosynthesis prevents adipocyte lipotoxicity on human osteoblasts in vitro

Abstract: Although increased bone marrow fat in age-related bone loss has been associated with lower trabecular mass, the underlying mechanism responsible remains unknown. We suggested that marrow adipocytes exert a lipotoxic effect on osteoblast function and survival through the reversible biosynthesis of fatty acids (FA) into the bone marrow microenvironment. We have used a two-chamber system to co-culture normal human osteoblasts (NHOst) with differentiating pre-adipocytes in the absence or presence of an inhibitor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
105
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(111 citation statements)
references
References 36 publications
3
105
0
3
Order By: Relevance
“…First, it is possible that increased marrow adiposity contributes to the increased skeletal fragility observed in clinical studies of TZDs. Co-culture experiments demonstrate that adipocytes induce osteoblast apoptosis via a paracrine mechanism (8) and inverse relationships between marrow fat and BMD have been reported in prospective studies on animals (9) and cross-sectional studies on humans (10). Decreased bone formation has been reported in both preclinical and clinical studies on TZDs (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it is possible that increased marrow adiposity contributes to the increased skeletal fragility observed in clinical studies of TZDs. Co-culture experiments demonstrate that adipocytes induce osteoblast apoptosis via a paracrine mechanism (8) and inverse relationships between marrow fat and BMD have been reported in prospective studies on animals (9) and cross-sectional studies on humans (10). Decreased bone formation has been reported in both preclinical and clinical studies on TZDs (3).…”
Section: Discussionmentioning
confidence: 99%
“…First, it is plausible that increased bone marrow fat induced by TZDs might detrimentally affect BMD. Evidence from in vitro studies suggests that adipocytes adversely influence bone cell function in a paracrine manner (8), prospective studies on animals report a contemporaneous increase in marrow fat and decrease in BMD (9), and correlative studies in humans suggest an inverse relationship between bone marrow fat and BMD (10). Second, it has been suggested that changes in bone marrow fat might artifactually alter measurement of BMD by dualenergy X-ray absorptiometry (DXA) (11).…”
Section: Introductionmentioning
confidence: 99%
“…Fat tissue is targeted by insulin and has a key role in insulin resistance. Adipocytes also secrete factors that inhibit the differentiation of osteoblasts (20), and a high-insulin …”
Section: Discussionmentioning
confidence: 99%
“…It acts an inhibitor of fatty acid synthase (FASN) by reacting with the keto-acyl synthase domain of FASN. Various studies have been performed to investigate the anti-tumor activity of cerulenin against the malignant neoplasms (Elbaz et al, 2010;Wang et al, 2008). The present study demonstrates the effects of the combination of cucurbitacin B and cerulenin on the rate of osteosarcoma cell proliferation, suppression of SENP5 expression and induction of apoptosis.…”
Section: Introductionmentioning
confidence: 72%